2017
DOI: 10.37358/rc.17.8.5786
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Adhesion of Composite Resins and Glass-Ionomer Cements in Open-Sandwich Technique

Abstract: The aim of this study was to assess the quality of the interface between dental root cement and some restorative materials used in the open sandwich technique. Standardised cavities were prepared on the buccal and oral surfaces of 30 human molars with the gingival margin situated in root cement. The teeth were randomly divided in 3 groups. Different materials combinations were used in buccal and oral cavities. In the control group, the cavities were filled only with composite resins (Filtek Z250-3M ESPE and Zm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Other authors reported frequent voids and fractures at the interface with gingival wall as well as cohesive fractures, concluding that all types of failures are present in glass ionomers cements, when using them in opensandwich technique [11].…”
Section: Resultsmentioning
confidence: 92%
“…Other authors reported frequent voids and fractures at the interface with gingival wall as well as cohesive fractures, concluding that all types of failures are present in glass ionomers cements, when using them in opensandwich technique [11].…”
Section: Resultsmentioning
confidence: 92%
“…An study which compare the the interface between enamel surfaces at the level of pit and fissure and the sealant with different cleaning procedures, with or without acid etching show that Concise White Sealant achieves a better enamel sealing than Dyract Seal when the teeth are treated with air abrasion or air polishing followed by etching [8]. The microhydrid composite resins have a significantly higher hardness than nano-hybrid composites or compomers [9,10] and in another study on top and on bottom surfaces Dyract eXtra showed the lowest hardness values [11]. Beresescu and all considered that particular types of restoring materials should be used in particular situation, depending on the location of the surfaces and the elastic characteristics of the materials and tooth structure [12].…”
Section: Resultsmentioning
confidence: 99%
“…ICDAS system was used for the detection of the incipient proximal caries. The definitions of ICDAS scores 02 and 03 for the proximal surfaces are as follows: score 02-distinct visual change in enamel visible when wet; score 03-initial breakdown in enamel due to caries without clinical visual signs of dentinal involvement [13].…”
Section: Experimental Part Materials and Methodsmentioning
confidence: 99%